COVID-19 Pandemic: Its Impact on Learning Motivation (The Fluctuation During Three Different Phases) - Natalya, Lina; Halim, Steven Victoria (Universitas Pendidikan Ganesha, 2021)
Education is a critical component that cannot be separated from an individual’s life. One of many important factors that could support, encourage, and give zeal in the learning process is motivation. The COVID-19 pandemic nowadays indirectly triggers a rapid and drastic change in the learning process, one of them being lecture that must be held online. This repeated cross-sectional research aimed to give a description regarding the fluctuation of students’ academic motivation level before, in the beginning, and until one-year after online learning. The data used in this study are primary and secondary data which are collected gradually and analyzed using Summary Independent Sample T-Test. The result of this research showed no significant differences in academic motivation before COVID-19 and during the early days of Learning From Home (µbefore = 4.777; µbeginning = 4.808; sig = 0.432), nevertheless, a significant decrease is observable one year after the online learning (µnow = 4.345; sigbefore-now = <0.001; sigbeginning-now = <0.001). The decrease in students’ academic motivation is certainly a crucial problem that is prioritized to be resolved. Hence, lecturers need to adapt with this change and create learning innovation in order to trigger students’ learning motivation.